METAPHOR IN THE POETRY “I AM A COLD HEART HUMAN” BY GALIH PANDHU (ON TELEGRAM) - fahdilla dilla; Anggie Nadia Harahap; Emeliya Sukma Dara Damanik; M. Farhan Husaini Siregar; Noni Sulistia (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to analyze the metaphors contained in the poem entitled